Mapeamento e análise crítica do processo de avaliação de investimentos: um estudo de caso - Montini, Mario José (2015)
The complex nature of investment decisions, which involves a wide range of factors, results that the decision maker rarely dominates all aspects that determine the quality of his/her decision. Decisions are made by individuals and their personal preferences may influence the outcome of their decision. Investment evaluation processes of an organization should help to ensure the manager that investment projects are analyzed according to a welldefined evaluation guide, in the same way and with due impartiality, in order to avoid that such personal preferences outweigh the "canons" of the organization. There are within the theory the necessary and sufficient tools for the investment evaluation, however, with regard to guides for investment evaluation, these are developed by the own organizations to meet their specific needs. In this study, an exploratory research seeks to conceptualize investment project and investment evaluation. Discounted cash flow methodology, capital asset pricing model and traditional metrics of investment evaluation are studied, as well as the aspects related to risk, uncertainty and irreversibility of real projects. Then, having as objective to extract from the theory an investment evaluation guide based on discounted cash flow methodology, several guides for evaluating investments were analyzed, looking for a systematization of procedures able to gather the essential steps of an evaluation, to ensure that these are carried out systematically. Afterwards, based on a case study, the resulting investment evaluation guide has been tested in a real case - previously assessed by a renowned consulting firm - and it has been confirmed that the said evaluation guide could have been successfully employed to evaluate the real case